Perceptions and Attitudes of Correctional Staff Toward ADHD—A Challenging Disorder in Everyday Prison Life - Buadze, Anna; Friedl, Nadine; Schleifer, Roman; Young, Susan; Schneeberger, Andres; Liebrenz, Michael (Frontiers in Psychiatry, 2021)
ADHD is a neurodevelopmental disorder that is associated with risk-taking behaviors, poor self-control and interpersonal difficulties. Affected individuals have an increased probability of involvement with the criminal justice system, contributing to a higher rate of arrest and imprisonment compared with the general population; they are also inadequately treated once sentenced. Because prison staff play a central role in the identification of inmates with mental disorders, they could well be key to improving provision of care. There is however little knowledge of the conceptions, perceptions and attitudes of prison staff towards ADHD. Such information could help to identify starting points for awareness training and further implementation of specific ADHD treatment. To bridge this gap, we undertook a study based on a qualitatively-driven mixed methods design, combining qualitative data collection in the form of narrative interviews with 19 prison staff from a Swiss correctional facility with quantitative data collection in the form of a survey that included the Attitudes Toward Prisoners scale. The interviews were analyzed with QSR NVIVO 11 and a qualitative content analysis approach was used to evaluate findings. Prison staff were generally aware of ADHD and its symptomology, believing it to a be “real”, but “fashionable” disorder and favoring hereditary-genetic or biological explanatory models for its development. They viewed inmates with ADHD rather negatively, as complicating correctional efforts, and perceived them as sticking out, as tying up more resources and as frequently being involved in confrontations. Our findings suggest that difficulties in pragmatic aspects of communication and language comprehension may be perceived “as not listening or following instructions”, creating additional tensions. Consequently, inmates with ADHD are more often exposed to disciplinary sanctions, such as solitary confinement - an intervention deemed “necessary” by staff. Therefore, staff training on ADHD might need to cover evidence on adverse effects. Non-pharmacological interventions for treatment were preferred and considered to be highly efficacious. Skepticism towards pharmacological treatment prevailed, even when benefits from stimulant medication were described. Interestingly, this skepticism was not the result of negative experiences with the misuse and diversion of stimulants. Acceptance of multimodal treatment among prison staff may require customized strategies.